2019
DOI: 10.1029/2019jd030330
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ice Cloud‐Precipitation Properties of Three Modes of Mesoscale Convective Systems During PECAN

Abstract: This study analyzes the precipitation and ice cloud microphysical features of three common modes of linear mesoscale convective systems during the Plains Elevated Convection at Night (PECAN) campaign. Three cases, one for each linear mesoscale convective system archetype (trailing stratiform, leading stratiform, and parallel stratiform precipitation), are selected. We focus primarily on analyzing ice cloud microphysical properties and precipitation rates (PRs) over the classified convective core (CC) and strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…For SP (Figures 12a and 12c), the log 10 N w values of the three stages were identical except for higher values above 8 km in the mature stage. The higher log 10 N w values indicated that more ice particles in the mature stage might be advected from convective regions by divergent air motions (Cui et al, 2019;Herzegh & Hobbs, 1980). Their D m profiles were consistent with the order of the stratiform vertical precipitation profiles (Figure 11a), with the smallest being in the developing stage and the largest in the mature stage.…”
Section: Drop Size Distributionsupporting
confidence: 60%
“…For SP (Figures 12a and 12c), the log 10 N w values of the three stages were identical except for higher values above 8 km in the mature stage. The higher log 10 N w values indicated that more ice particles in the mature stage might be advected from convective regions by divergent air motions (Cui et al, 2019;Herzegh & Hobbs, 1980). Their D m profiles were consistent with the order of the stratiform vertical precipitation profiles (Figure 11a), with the smallest being in the developing stage and the largest in the mature stage.…”
Section: Drop Size Distributionsupporting
confidence: 60%
“…Through the combination of the Next Generation Radar (NEXRAD) network and the Geostationary Operational Environmental Satellite system (GOES) observations, Feng et al 2011developed a hybrid cloud classification algorithm that objectively separates the convective systems into the components of convective core (CC), stratiform rain (SR), and anvil clouds (AC). The SR regions have the largest coverage of warm-season rainfall over the midlatitudes, while the CC regions (corresponding to the precipitation type of CR) account for the most intense precipitation (Cui et al 2019). Feng et al (2012) also found that the CR rain rate is almost an order of magnitude higher than SR, causing a surge in accumulated precipitation within a short time period and possibly resulting in flooding events.…”
Section: E Separation Of Convective Versus Stratiform Rainmentioning
confidence: 94%
“…The major NEXRAD products used in this study include: reflectivity data, and the dual‐pol products of specific differential phase ( k dp ), differential reflectivity ( Z dr ), and cross‐correlation ( ρ hv ). The k dp , Z dr , and ρ hv products illustrate the vertical and horizontal interaction of the radar beam with hydrometeors (Brauer et al., 2020; Cifelli et al., 2010; Cui et al., 2019; Fridlind et al., 2019; Kumjian, 2013; Li & Mecikalski, 2012; Tian et al., 2020). For example, a falling raindrop is considered to have a larger horizontal than vertical semi‐axis (“hamburger shape”) with positive k dp and Z dr values.…”
Section: Methodsmentioning
confidence: 99%